Interfacial electronic properties between PtSe 2 and 2D metal electrodes: a first-principles simulation - Tian, Xinyue; Zhang, Wenfei; Zhang, Guang-Ping; Li, Zong-Liang; Wang, Chuan-Kui; Wang, Minglang (Physical chemistry chemical physics : PCCP, 2023)
Monolayer (ML) PtSe 2 is a two-dimensional (2D) semiconductor with a modest band gap and high carrier mobility, and it is a promising 2D material for electronic devices. Finding suitable metal electrodes is a key factor in fabricating high-performance PtSe 2 field effect transistors (FETs). In this study, a series of 2D metals, transition metal dichalcogenides (NbSe 2 , TaS 2 ), borophene, and MXenes (V 2 C(OH) 2 , V 2 CF 2 , Nb 2 C(OH) 2 , Nb 2 CF 2 , Nb 2 CO 2 , Hf 2 C(OH) 2 , Hf 2 CF 2 ) were used as electrodes for FET fabrication. The interfacial electronic properties of electrodes and PtSe 2 were studied in both the vertical and lateral directions using the ab initio method. In the vertical direction, PtSe 2 formed ohmic contacts with most of the 2D metals except for Nb 2 CF 2 and Hf 2 CF 2 . Specifically, in the cases of Nb 2 CF 2 and Hf 2 CF 2 , p- and n-type Schottky contacts were formed with Schottky barrier heights (SBHs) of 0.48 eV and 0.02 eV, respectively. In the lateral direction, PtSe 2 with contacting Hf 2 CF 2 and V 2 C(OH) 2 electrodes formed n-type Schottky contacts with SBHs of 0.14 eV and 0.09 eV, respectively. In the cases of TaS 2 and Nb 2 CF 2 electrodes, p-type Schottky contacts with SBHs of 0.35 eV and 0.29 eV, respectively, were formed. Moreover, n-type ohmic contacts were observed when Hf 2 C(OH) 2 and Nb 2 C(OH) 2 electrodes were applied, and p-type ohmic contacts were formed when borophene, NbSe 2 , Nb 2 CO 2 , and V 2 CF 2 electrodes were used. This work reports a systematic investigation of ML PtSe 2 -2D metal interfaces and serves as a practical guide for selecting electrode materials for PtSe 2 FETs.